2010
DOI: 10.1097/htr.0b013e3181dc82fa
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Oriented Approach Exploring the Relationship Between Visual and Vestibular Disturbances and Problems of Higher-Level Mobility in Persons With Traumatic Brain Injury

Abstract: Dizziness and impaired balance are common complaints after traumatic brain injury as a result of injuries to many systems. Ambient visual and vestibular system impairments are strong contributors to imbalance and dizziness, often leading to problems with spatial orientation and gaze stability during movement. The purpose of this review is to provide an overview of visual-vestibular impairments common to traumatic brain injury and summarize the contribution impairments in these systems will have on higher-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6] Impairment of postural stability is particularly evident in visually crowded environments (ie, places with a large number of moving objects). 7,8 These posture-related deficits increase the risk of falling and the associated secondary trauma. 9,10 Considering that TBI survivors constitute one of the largest groups of people with disability worldwide, 11 investigations of potentially destabilizing conditions and strategies for reducing postural instability are important in the context of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Impairment of postural stability is particularly evident in visually crowded environments (ie, places with a large number of moving objects). 7,8 These posture-related deficits increase the risk of falling and the associated secondary trauma. 9,10 Considering that TBI survivors constitute one of the largest groups of people with disability worldwide, 11 investigations of potentially destabilizing conditions and strategies for reducing postural instability are important in the context of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Anywhere from 23-81% of patients report dizziness in the days following injury. [1][2][3] An initial presentation of dizziness can be a predictor of prolonged recovery from concussion, both in athletic and general populations. [4][5][6] The vestibular system's regulation of balance, spatial orientation, and gaze stability plays a key role in athletic tasks and many activities of daily living.…”
Section: Introduction/clinical Scenariomentioning
confidence: 99%
“…Although several reviews have been conducted on interventions for clients with ABI with VD, few have examined assessments of this population in the rehabilitation setting. Of the 10 reviews conducted on evaluation tools for clients with stroke and TBI (Akhand et al, 2019a;Akhand et al, 2019b;Aksionoff & Falk, 1992;Hanna et al, 2017b;Hepworth et al, 2015;Hunt et al, 2016;Peterson, 2010;Pillai & Gittinger, 2017;Ventura et al, 2014;Ventura et al, 2015), none encompassed all conditions of adult ABI, most focused on one area of VD (e.g., unilateral spatial neglect [USN]). Eight reviews (Hanna et al, 2017a;Peterson, 2010) came from the fields of ophthalmology and neurology.…”
mentioning
confidence: 99%
“…Of the 10 reviews conducted on evaluation tools for clients with stroke and TBI (Akhand et al, 2019a;Akhand et al, 2019b;Aksionoff & Falk, 1992;Hanna et al, 2017b;Hepworth et al, 2015;Hunt et al, 2016;Peterson, 2010;Pillai & Gittinger, 2017;Ventura et al, 2014;Ventura et al, 2015), none encompassed all conditions of adult ABI, most focused on one area of VD (e.g., unilateral spatial neglect [USN]). Eight reviews (Hanna et al, 2017a;Peterson, 2010) came from the fields of ophthalmology and neurology. Hepworth et al (2015) and Pillai and Gittinger (2017) concluded that a combination of evaluation tools may be required for a thorough evaluation of VD in stroke and TBI.…”
mentioning
confidence: 99%